An Overview of the Development and Impact of MBA Programs in Pakistan (Journal of Social Sciences Review, 2024)
This article discusses Pakistan's MBA program development and impact. The report examines Pakistan's MBA education from its beginnings to its widespread adoption. Through academic sources, institution data, and industry interviews, this is achieved. MBA programs are driven by globalization, the company's need for managerial skills, and government efforts to boost higher education. The essay also covers Pakistani business schools' MBA programs, instructional methods, and accreditation systems. This study examines how MBA education affects students, employers, and society. The study uses qualitative and quantitative approaches to examine how Master of Business Administration degrees affect employment opportunities, managerial abilities, and socioeconomic situations. This paper analyzes Pakistani MBA schools' quality assurance, instructor shortage, and industry alignment issues. The study also examines how digitization, sustainability, and entrepreneurship may affect MBA education. This article discusses the impact of MBA programs on Pakistan's corporate environment and the purpose of increasing human capital. Research, collaboration, and creativity are essential to keeping MBA education relevant and effective in changing socioeconomic conditions, according to the statement.
Keywords: Pakistan.; Management Sciences; MBA; Business